Interfaith Marriage: A Legal Analysis Through ‘Illat and Maqashid Syariah - Sahrul Hanafi; Basyarudin (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2026)
Interfaith marriage is a sensitive issue that continues to spark controversy in Islamic family law, particularly when analyzed through the perspectives of text-based Islamic legal philosophy (nash), legal rationality ('illat), and the objectives of Sharia (maqashid syariah). This study aims to conduct an in-depth examination of the issues surrounding interfaith marriage in the context of pluralistic Indonesia. Using a qualitative method with a normative-philosophical approach, this study analyzes classical and contemporary literature as well as interpretations of maqashid syariah within the framework of legal pluralism. The results indicate that the prohibition on interfaith marriage is not merely normative-theological in nature but is grounded in rational justifications related to the protection of religious belief, household stability, and children’s education. From the perspective of maqashid al-sharia, this prohibition functions as a preventive instrument to safeguard religion (hifz al-din) and lineage (hifz al-nasl). However, Indonesia’s pluralistic social reality introduces new dynamics regarding human rights, necessitating a reinterpretation of the law without disregarding the fundamental principles of sharia. This study contributes by developing an operational framework for applying maqashid al-sharia to cases of interfaith marriage in Indonesian courts, specifically through the formulation of three evaluation criteria for testing the 'illat. This study provides an analytical framework that balances classical fiqh norms and contemporary social needs, and enriches the literature on Islamic family law in a multireligious society through a contextual dialectic of 'illat and maqashid. Keywords: Interfaith Marriage; Islamic Legal Philosophy; 'Illat Analysis; Maqashid al-Sharia; Islamic Family Law